Factors Influencing Farmer’s Decisions to Switch Apple to Orange Farming in Bulukerto Village, Bumiaji Sub-district, Batu City - Talitakum, Talitakum; Roidah, Ida Syamsu; Syah, Mirza Andrian (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
The agricultural sector is a strategic sector and has an important role in national economic development and community survival. Each region certainly has different natural resource potential. Batu City is one of the apple-producing areas in East Java Province. Over time, there was a decline in apple productivity, which caused farmers to decide to transfer the commodity. This study aims to analyze the phenomenon of switching farms, identify influencing factors, and analyze the effect of commodity transfer on farmers' income. The determination of the location of the study was carried out by simple random sampling. The sampling method used the Slovin formula, and the sample used in this study was 60 farmers. Logistic regression analysis was used to analyze the relationship between one or more independent variables with categorical dependent variables, and the Wilcoxon Signed Rank Test is a method of non-parametric statistic that aims to determine whether or not there is a difference between 2 pairs of data on an ordinal or interval scale. The results showed that the impetus that made farmers switch commodities to oranges were: (1) climate, changes in market prices, changes in consumer tastes, decreased crop yields, decreased apple quality, pests and diseases of apple plants. (2) Factors that directly influence farmers' decision-making in transferring commodities are age, education, number of family dependents, farming experience, citrus farm income, and care/maintenance. (3) There is a significant difference between the income of farmers who farm apples and farmers who farm oranges. The average income of apple farmers is IDR 13,158,332/Year, while orange farmers have an average income of IDR 14,703,333/Year.